ERROR CORRECTING TECHNIQUES IN LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Error correction is a crucial component of language teaching because it supports learners’ linguistic accuracy, raises their awareness of target forms, and improves long-term communicative ability. This article examines theoretical foundations of error correction, types of errors, and major corrective feedback techniques. Approaches such as explicit correction, recasts, clarification requests, metalinguistic feedback, elicitation, and repetition are analyzed through the lens of second language acquisition research. The paper also discusses affective considerations, timing, and teacher–learner interaction. Recommendations for effective, research-based correction practices conclude the article.